PENGARUH SMALL SIDED GAMES TERHADAP KELINCAHAN DALAM PERMAINAN FUTSAL DI EKSTRAKULIKULER SMPN 1 DARMA - Elang Fauzan; Rizki Setiasandi; Ramdhani Rahman (STKIP Muhammadiyah Kuningan, 2021)
This study aims to improve the agility of the futsal extracurricular participants at SMPN 1 Darma through the small side game training method. This research is an experimental study which was carried out for approximately one month, with the intensity of meeting three times a week. In total there are 4 weeks with a frequency of exercise 3 times in 1 week in August-September 2021. Data were collected through pretest and posttest. Data were analyzed using SPSS. The results showed that the small side games method was very suitable to be applied to futsal extracurricular participants at SMPN 1 Darma. Because with the small side games training program, extracurricular participants can improve agility. The conclusion is that small side games can increase the agility of futsal extracurricular participants.